1994
DOI: 10.1002/mrm.1910320405
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of absolute metabolite concentrations in human tissue by 31P MRS in vivo. Part II: Muscle, liver, kidney

Abstract: Absolute metabolite concentrations were assessed in the muscle, the liver, and the kidney of healthy human volunteers by 31P MRS. Fully relaxed in vivo spectra were acquired with a surface coil and were localized with an adiabatic ISIS pulse sequence. The spectra were quantified with a subsequent measurement of a calibration phantom and were processed iteratively in the time domain. The following mean metabolite concentrations (mmol/liter) were measured in the resting male calf muscle (n = 9), in the fasting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
78
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 28 publications
14
78
3
Order By: Relevance
“…5a,f (not drawn to the same scale). The relaxation rates for phosphorus resonances originating from muscle are considerably longer than those from liver [19], which adds to the discriminatory power of liver detection. Figure 5a, g (not drawn to the same scale) shows a typical image-guided spectrum of the human liver using volume selective excitation, although with worse than typical inclusion of PCr signal.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…5a,f (not drawn to the same scale). The relaxation rates for phosphorus resonances originating from muscle are considerably longer than those from liver [19], which adds to the discriminatory power of liver detection. Figure 5a, g (not drawn to the same scale) shows a typical image-guided spectrum of the human liver using volume selective excitation, although with worse than typical inclusion of PCr signal.…”
Section: Resultsmentioning
confidence: 98%
“…This is especially the case when the sequence is improved by adding more steps in the phase cycle in order to further improve the accuracy of the volume selection [22]. In any case many reports show spectra of apparently excellent volume selection, discriminating resonances obviously originating from peripheral muscle tissue [19].…”
Section: If [Pme]/[pde] Is Decreased Is [Pme] Then Decreased? or Is mentioning
confidence: 98%
“…[32][33][34][35][36][37] In addition to MRS-dependent differences, the great interindividual variability within and across these studies could be due to the nutritional status and variations of age and BMI. To overcome such influences, we controlled for dietary intake and matched the controls for age and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been demonstrated that this is, in principle, technically possible. 4,7,18 Due to the long acquisition times and the large measured volumes, these methods have not, as yet, been integrated into our clinical protocols.…”
Section: Methodological Aspectsmentioning
confidence: 98%